Do low back pain changes correlate with sagittal lumbar alignment changes after total hip replacement arthroplasty? - Abdalhadi Alobidi, Firas (Journal of the Faculty of Medicine Baghdad, 2015)
Background: The hip joint and lumbar spine are both anatomically and functionally closely related as had shown by many authors. So the abnormality in one area can affect the other e.g. hip joint osteoarthritis can cause lumbar sagittal malalignment and backache.Objectives: is to see if there is significant improvement in backache after total hip replacement? And which degree of backache improvement is associated with significant changes in lumbar lordosis?Methods and patients: a prospective open trial study was performed on 30 patients who had severe hip osteoarthritis and chronic low back pain. Total hip replacement was performed to all patients. Backache and lumbar lordosis were measured by visual analogue scale and Cobb’s angle respectively both before and 6 months after surgery. Patients were divided into 3 groups according to grade of improvement in backache after surgery.Results: The improvement in low back pain after surgery was statistically significant for all patients and for each group separately, while the changes in lumbar lordosis were not statistically significant neither for all patients nor for any group separately.Conclusions: total hip replacement surgery has significant positive effect on backache. There is no significant correlation between improvement in backache and changes in lumbar lordosis.